ANALYSIS OF INDEPENDENT CURRICULUM MANAGEMENT POLICY FROM THE PERSPECTIVE OF ISLAMIC EDUCATION - Muhammad Durrin Ni’am (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The Independent Curriculum  policy, initiated by the Ministry of Education, Culture, Research, and Technology, brings about major changes in the national education system by emphasizing the Pancasila-based student profile and learning autonomy. For Islamic educational institutions, this policy requires a managerial and pedagogical reorientation to remain aligned with Islamic values. This study aims to analyze the management of the implementation of the Independent Curriculum from an Islamic education perspective, specifically in interpreting the policy and implementing strategies at the educational unit level. Using a qualitative case study approach, data was obtained through document analysis, n-depth interviews, and participatory observation in several Islamic schools implementing the Independent Curriculum. The research results show that Islamic educational institutions adaptively interpret and implement the Independent Curriculum while maintaining their Islamic identity. The strategies implemented include; Integrating Islamic values into all subjects through a monotheistic epistemological approach, Strengthening the role of Islamic Religious Education and Character Education, and Developing Islamic-influenced projects, such as waqf-based social entrepreneurship. In conclusion, the management of the Independent Curriculum in Islamic educational institutions is adaptive, creative, and contextual, guided by an Islamic educational vision. The implication is that policymakers need to understand the characteristics of Islamic institutions, while educational administrators are required to have strategic capacity to manage change without losing their Islamic mission.